Analysis of Induced Mutation in Rhizobium Using Different Azo Dyes by RAPD PCR - Sadeeshkumar, R (International Journal of Pharmaceutical & Biological Archive, 2012)
Analysis of Induced Mutation in Rhizobium Using Different Azo Dyes by RAPD PCR